Respuesta :
Answer:
Step-by-step explanation:
f(x) = –2x² + 12x + 5
= -2 (x² - 6x - 5/2)
= - 2 ( x² -2(3)x +9 - 9 - 5/2)
= - 2 ( (x - 3)²-23/2)
f(x) = - 2 ( x - 3)²+23 .....vertex form
the vertex is : (3 : 23) Maximum at (3, 23) because a = -2 and a< 0
Answer:
Maximum at (3, 23)
Step-by-step explanation:
[tex]f(x) = -2x^2 + 12x + 5[/tex]
f(x)= a(x-h)^2 +k , where (h,k) is the vertex
Apply completing the square method to find vertex
[tex]f(x) = -2x^2 + 12x + 5[/tex]
[tex]f(x) = -2(x^2 -6x)+ 5[/tex]
Let take half of coefficient of x is -6 divide by 2 is -3
square it (-3)^2 is 9
Add and subtract 9
[tex]f(x) = -2(x^2 -6x+9-9)+ 5[/tex]
Take out -9 and multiply by -2
[tex]f(x) = -2(x^2 -6x+9)+18+ 5[/tex]
[tex]f(x) = -2(x^2 -6x+9)+23[/tex]
Now factor the parenthesis part
[tex]f(x) = -2(x-3)^2+23[/tex]
The value of h=3 and k=23
So vertex is (3,23)
The value of 'a' is -2, it means the parabola is upside down. so vertex is maximum
vertex is maximum at (3,23)